High degree of atrioventricular block during mandibular cystectomy in a healthy adult patient - Takaya Ito; Sakiko Okura; Chihiro Suzuki; Yushi Abe; Yoshihisa Morita; Shigeru Maeda (Elsevier, 2022)
During mandibular cystectomy under general anesthesia in a 46 year old male, classified ASA-PS1, a T wave peak was noted. This was followed by ST segment elevation and a high degree of atrioventricular block with severe bradycardia. Chest compression was performed immediately and sinus rhythm, with regular heart rate (HR), was observed to recover soon after. ST segment depression remained; after return of spontaneous circulation, it recovered to normal levels in 50 min. Based on the electrocardiogram changes, vasospastic angina, related to the right coronary artery, was the prime suspect. It is recommended that vasospastic angina should be prepared for in the perioperative period, even when there seems to be no risk of it.